1995
DOI: 10.1084/jem.181.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Fas ligand mediates activation-induced cell death in human T lymphocytes.

Abstract: Suml'l'lary A significant proportion of previously activated human T cells undergo apoptosis when triggered through the CD3/T cell receptor complex, a process termed activation-induced cell death (AICD). Ligation of Fas on activated T cells by either Fas antibodies or recombinant human Fas-ligand (Fas-L) also results in cytolysis. We demonstrate that these two pathways of apoptosis are causally related. Stimulation of previously activated T ceils resulted in the expression of Fas-L mILNA and lysis of Fas-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
465
0
11

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 873 publications
(491 citation statements)
references
References 44 publications
15
465
0
11
Order By: Relevance
“…It may be concluded from the concomitantly high levels of IL-10 mRNA and IFN-γ mRNA in CD8 + TIL that Th1 as well as Th2 lymphocytes are activated, which is in accordance with a recently published study showing also high levels of IL-10 and IFN-γ mRNA in TIL from non-small cell lung cancer and ovarian cancer biopsies (Asselin-Paturel et al, 1998;Pisa et al, 1992). Since it has recently been shown that in vitro activated T cells express high levels of FasL mRNA and protein (Alderson et al, 1995;Brunner et al, 1995;Dhein et al, 1995;Martinez-Lorenzo et al, 1996), the elevated FasL mRNA levels in RCC TIL also indicate an immunological activation of these lymphocytes.…”
Section: Discussionsupporting
confidence: 90%
“…It may be concluded from the concomitantly high levels of IL-10 mRNA and IFN-γ mRNA in CD8 + TIL that Th1 as well as Th2 lymphocytes are activated, which is in accordance with a recently published study showing also high levels of IL-10 and IFN-γ mRNA in TIL from non-small cell lung cancer and ovarian cancer biopsies (Asselin-Paturel et al, 1998;Pisa et al, 1992). Since it has recently been shown that in vitro activated T cells express high levels of FasL mRNA and protein (Alderson et al, 1995;Brunner et al, 1995;Dhein et al, 1995;Martinez-Lorenzo et al, 1996), the elevated FasL mRNA levels in RCC TIL also indicate an immunological activation of these lymphocytes.…”
Section: Discussionsupporting
confidence: 90%
“…All other ISD tested did not modulate CD95-sensitivity in Jurkat cells or in peripheral T cells. AICD in Jurkat T cells [45] and peripheral human T cells [46] is mediated mainly by an increased production and release of CD95L. Therefore we hypothesized that ISD might induce an accelerated AICD by increased CD95L production.…”
Section: Discussionmentioning
confidence: 99%
“…Activated T cells in vitro express Fas ligand (FasL), a natural ligand for Fas, and efficiently kill Fas þ target cells [30,31], indicating that the regulation of the interaction of Fas and FasL is important in the development of goitre and hyperthyroidism in patients with GD. Considered together, these results suggest that the goitrogenic activity of TSAb in GD may, in part, be associated with the inhibitory effect on Fas-mediated apoptosis of thyrocytes.…”
Section: Discussionmentioning
confidence: 99%